The effectiveness of GenoType MTBDRplus using in the diagnosis of tuberculosis in Zaporizhzhia region - R. M. Yasinskyi; O. M. Raznatovska; O. V. Konakova; O. M. Kamyshnyi; N. A. Rokhmanova; A. V. Klymenko; Jean-Luc Berland; Marie Gauhier (Patologìâ)
The method GenoType MTBDRplus, v.2 allows to study clinical material from positive and negative smears, to examine patients with new and previously treated cases of tuberculosis pulmonary and extrapulmonary localization. But now there is a small amount of researches concerning the use of this method in the diagnosis of tuberculosis.